ISSUES IN DESIGNING PILES FOUNDATION FOR POTENTIALLY EXPLOSIVE FACILITIES AT PRIKUMSKY PLASTICS PLANT (JSC STAVROLEN) IN CITY OF BUDENNOVSK - Boris F. Galay; Vitaly V. Serbin; Viktoria S. Plakhtyukova (Вестник Северо-Кавказского федерального университета)
The potentially explosive facilities of Russia’s largest oil-chemical plant were initially designed on improper piles in subsiding soils Unlike Atommash (City of Volgodonsk, Russia), the emergency in Budennovsk was averted at the stage of construction, and in some cases the pile construction was rejected. It is recommended that the fundament be examined after 40 years of being used in aggressive sulfate ground waters and increased seismic activity of the site.